Responses of growth and yield of 'Diacol Capiro' potatoes to application of silicate fertilizer amendments - Torres-Hernández, David Fernando; Pinzón-Sandoval, Elberth Hernando; Balaguera-López, Helber Enrique; Silva-Parra, Amanda; Galvis-Quintero, Jesús Hernando (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
The potato crop (Solanum tuberosum L.) is considered as one of the main agricultural products in the cold climate regions of Colombia. However, these areas often feature acidic soils with Andean properties, leading to limited availability of essential elements like phosphorus, calcium, magnesium, and beneficial elements such as silicon. Consequently, we assessed the impact of applying increasing doses of three silicate fertilizer amendments on the growth and production parameters of the 'Diacol Capiro' potato within an acidic desaturated soil located in Soraca (Colombia). Two evaluation cycles were executed, each adopting a completely randomized design with 10 treatments. These treatments comprised three doses (300, 600, and 900 kg ha-1) of three amendments (thermal phosphate, double calcium, and magnesium silicate, and Triple 30® amendment (Rio Claro, Medellin)), in addition to a control treatment. Growth variables, encompassing fresh and dry biomass accumulation in aboveground and root components, leaf thickness, leaf area, and total yield, were evaluated. Statistical differences were evident among treatments (P<0.05) for all growth variables and total yield. A discernible response surfaced concerning silicate fertilizer dosage and type. Particularly, the double calcium and magnesium silicate, administered at a dosage of 900 kg ha-1, elicited the most favorable growth and production (61.8±4.1 t ha-1) response. This underscores the potential of silicate fertilizers as a noteworthy alternative for enhancing growth and production in potato plants under the specific conditions of this study.